All that Glitters: Sport, BP, and Repression in Azerbaijan ('The great coming out Party of Azerbaijan' and 'What the marriage has created'). (1st June 2016) - Hughes, Emma; Marriott, James
All that Glitters was first published by Platform to mark the Opening Ceremony of the 2015 European Games in Baku. The inaugural European Games was about much more than medals. Held in Azerbaijan at the height of a systematic crackdown on human rights and democracy, the Games were the first of a series of international sporting events the country hosted. This reprint of excerpts from All That Glitters explores how the Games belonged to Azerbaijan's Aliyev regime and the British oil company BP and how sport was co-opted in the service of a dynasty and fossil fuels. A sequel to Platform's The Oil Road, this publication returns readers to Azerbaijan's capital, where a new generation of lawyers, journalists, politicians and activists struggles for its country's freedom. All That Glitters unpicks the heady mix of sport, repression and hydrocarbons that is blinding the world to the grim reality behind the showcase of Baku.